Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting. (Policy Papers; Policy Paper ;, 2014)
The Managing Director's Global Policy Agenda (GPA) presented to the IMFC in October identified a range of actions needed to prevent growth from settling into a 'new mediocre' with unacceptably low job creation and inclusion. These actions included managing eventual monetary normalization in advanced economies and its effects on other economies, growth-friendly fiscal policies to enhance the quality of public expenditure and reduce distortions in revenue collection, policies to safeguard financial stability while strengthening credit transmission, structural reforms to buttress productivity and strengthen growth, and increasing investment in infrastructure. The GPA also outlined how the Fund would support the membership through assessments and policy advice provided in the context of multilateral and bilateral surveillance, capacity building, and financial support.